Modelling and control problems of distillation column. - Jafri, M. Noman. (University of Ottawa (Canada), 1964)
A linearised dynamic model of a 10-plate binary distillation column was obtained by perturbation technique. The control of the column was considered by two methods: one manipulated variable (reflux) control and two manipulated variables (reflux and reboil) control. These methods were studied on an analog computer. In both cases optimal parameters of the controllers were obtained by integral of the square error criterion for disturbances in the feed composition. The effect of interaction in two manipulated variable control was also studied. It was concluded that two manipulated variable control was practical since it ensures reliability in the operation of the column.
Keywords: Engineering, Electronics and Electrical.